Groundwater pollution risk assessment based on groundwater vulnerability and pollution load on an isolated island. (February 2022) - Zhao, Xiaoning; Wang, Daqing; Xu, Haoli; Ding, Zhibin; Shi, Yue; Lu, Zhao; Cheng, Zijian
Abstract: Prolonged leakage of surface pollutants has an impact on groundwater quality, especially in shallow groundwater. This paper proposes a new method combining Modflow and geographic information system data for groundwater pollution risk assessment. First, hydrogeological information of the study area was obtained through a field investigation and data referencing, and the groundwater flow field in the study area was constructed. The actual drilling water level data were then used for verification. A groundwater solute transport model was constructed based on the groundwater flow field, combined with pollution source sampling and detection data. Finally, based on the simulation of the migration value of pollutants, the groundwater in the study area was evaluated by constructing a groundwater pollution risk assessment system that combined groundwater vulnerability and pollution load. The results showed that in the study area, the heavy-risk area accounted for 38%, the high-risk area accounted for 29%, the medium-risk area accounted for 22%, and the low-risk area accounted for 11%. Approximately 70% of the area was rated as high-risk or above, indicating that the groundwater in the study area was more susceptible to surface pollutants. Once groundwater is contaminated, recovery is difficult; therefore, groundwater pollution risk assessments are necessary. The groundwater pollution risk assessment system constructed by the groundwater numerical simulation and multi-index comprehensive evaluation method has significance as a reference for regional groundwater pollution risk identification and scientific management. Graphical abstract: Image 1 Highlights: A new method is proposed for groundwater pollution risk assessment. The new method combines Modflow and GIS data. The groundwater flow field on Wailingding Island was constructed and verified. A groundwater solute transport model was constructed. ∼70% of the area was ≥ high-risk; groundwater is susceptible to surface pollutants.